Deviation from the sech2 superradiant emission law in a two-level atomic system - Gonçalves, A. Edson; Mizrahi, Salomon S.; Pimentel, B. M. [UNESP] (American Physical Society (APS), 1990)
The atomic superradiant emission is treated in the single-particle mean-field approximation. A single-particle Hamiltonian, which represents a dressed two-level atom in a radiation field, can be obtained and it is verified that it describes the transient regime of the emission process. While the line-shape emission for a bare atom follows the sech2 law, for the dressed atom the line shape deviates appreciably from this law and it is verified that the deviation depends crucially on the ratio of the dynamic frequency shift to the transition frequency. This kind of deviation is observed in experimental results. © 1990 The American Physical Society.